APPLY THE CASE LAW OF THE EUROPEAN COURT OF HUMAN RIGHTS TO UNDERSTAND THE GUARANTEES OF ARTICLE 5 OF THE EUROPEAN CONVENTION ON HUMAN RIGHTS - Tretyakov, Dmytro (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: this article aims at highlighting and structuring the most important principles of Article 5 of the European Convention on Human Rights (Convention), which guarantees the right to freedom and security of person, based on examples of judgments delivered by the European Court of Human Rights (ECHR) on the applications against Ukraine. The methodological basis of the study consists of general scientific methods of cognition, used by the author for identification of the main principles developed by the ECHR in its case-law on protection of the right to personal liberty under Article 5 of the Convention. Results: the main principles of Article 5 are illustrated by cases against Ukraine, which allows better understanding of those principles in the context of the legal system of Ukraine. Discussion: the article examines the case-law of the ECHR against Ukraine, in which the basic principles of understanding and interpretation of guarantees contained in Article 5 of the Convention are discussed. It starts with the main rule, which is presumption in favour of liberty. Any detention is an exception to that rule and although the right to liberty is not absolute, it can be interfered with only in clearly defined cases, listed in paragraph 1 of Article 5. Any deprivation of liberty shall also be lawful, which implies the existence of relevant legal framework. Such framework shall be in compliance with the principles enshrined in Article 5 and the authorities in their turn shall act in good faith and in compliance with the procedure prescribed by such legal framework. Furthermore, any deprivation of liberty shall be free of arbitrariness. Detained persons shall be informed about the reasons of their arrest, which would allow them to present arguments for their release to the court, which shall exercise immediate and direct control over any instance of deprivation of liberty. Domestic authorities shall advance sufficient reasons for keeping a person in custody and valid reasons for deprivation of liberty shall exist throughout the period of detention. The article further discusses the alternatives for detention and the procedural guarantees to those who were deprived of their liberty. It finally describes the requirements of compensation for unlawful detention.